Open access medical journals: benefits and challenges - Wang, Jenny Z.; Pourang, Aunna; Burrall, Barbara (2019)
The world of medical science literature is ever increasingly accessible via the Internet. Open access online medical journals, in particular, offer access to a wide variety of useful information at no cost. In addition, they provide avenues for publishing that are available to health care providers of all levels of training and practice. Whereas costs are less with the publishing of online open access journals, fewer resources for funding and technical support also exist. A recent rise in predatory journals, which solicit authors but charge high fees per paper published and provide low oversight, pose other challenges to ensuring the credibility of accessible scientific literature. Recognizing the value and efforts of legitimate open access online medical journals can help the reader navigate the over 11,000 open access journals that are available to date.
DOI: 10.1016/j.clindermatol.2018.09.010
Keywords: Open access; Medical; Journals; Benefits